PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN WORDWALL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA AKUNTANSI - Laoren Valerina; Rini Herliani; La Hanu; Andri Zainal; Ulfa Nurhayati (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The problem in this study is the low activity and learning outcomes of class XI AKL 1 students of SMK Negeri 6 Medan. The purpose of this study was to determine the increase in student activity and learning outcomes through the application of the Role Playing learning model assisted by Wordwall. This study is a Classroom Action Research (CAR) which was carried out in two cycles with 28 students as subjects. Data were collected through observation and tests, then analyzed quantitatively. The results showed that the percentage of students categorized as active and very active increased from 53.56% in cycle I to 100% in cycle II. Student learning outcomes also increased, indicated by an average pre-test score of 57.85 with 14.28% completeness, increasing to 80.07 with 57.14% completeness in cycle I, and reaching 92.46 with 100% completeness in cycle II. Thus, the application of the Role Playing model assisted by Wordwall is proven to be able to increase student activity and learning outcomes. The Wordwall-assisted Role Playing model can be used as an alternative, innovative learning strategy to improve student activity and learning outcomes. This study's limitations lie in the subject coverage, which only involved one class and one subject.